Playing Endgame or wearing the inside out. A work af art attempting to escape its ontological concept - Rybinska, Krystyna (Aktualitet - Litteratur, kultur og medier, 2018)
Krystyna Rybinska, Faculty of Philosophy, University of Gdansk: "Playing Endgame or wearing the inside out. A work af art attempting to escape its ontological concept"